Single-cell RNA sequencing reveals the role of immune-related autophagy in spinal cord injury in rats - Li, Erliang; Yan, Rongbao; Yan, Kang; Zhang, Rui; Zhang, Qian; Zou, Peng; Wang, Huimei; Qiao, Huan; Li, Shuang; Ma, Qiong; Liao, Bo (Frontiers in Immunology, 2022)
Spinal cord injury refers to damage to the spinal cord due to trauma, disease, or degeneration; and the number of new cases is increasing yearly. Significant cellular changes are known to occur in the area of spinal cord injury. However, changes in cellular composition, trajectory of cell development, and intercellular communication in the injured area remain unclear. Here, we used single-cell RNA sequencing to evaluate almost all the cell types that constitute the site of spinal cord injury in rats. In addition to mapping the cells of the injured area, we screened the expression of immune autophagy-related factors in cells and identified signaling pathways by the measuring the expression of the receptor‒ligand pairs to regulate specific cell interactions during autophagy after spinal cord injury. Our data set is a valuable resource that provides new insights into the pathobiology of spinal cord injury and other traumatic diseases of the central nervous system.